KOREYS TILI LINGVOMADANIYATIDA “HASAD” HISSIY KONSEPTI - Sa’dullayeva, O.; Kim, N. (SCIENCE and SOCIETY, 2019)
The Korean language is rich in stableset expressions, based on the national characteristics, we can say that most Koreans speak passionately and emotionally. If we speak about an emotional concept, the feeling of jealousy is a negative emotion that breaks the human heart and destroys it. As it was mentioned above, the key to research is that the concept of emotions is an important factor in the natural perception of the Korean language and literature. For example, in Korean, there is a myth that spring comes and snow melts. The warmth and joy of blooming flowers evoke cool envy. This Korean metaphor is essential for understanding and exploring the emotional concept of «jealousy» in Korea.
Keywords: language; culture; jealousy; linguoculturology; emotion; conception; concept; feeling; opinion